ISOLATION AND CHARACTERIZATION OF ANTIOXIDANT COMPOUNDS FROM ETHYL ACETATE AND METHANOL EXTRACTS OF GARCINIA DAEDALANTHERA PIERRE LEAVES - Puspitaningrum, Anisa; Elya, Berna; ., Katrin (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to isolate and characterize the compounds responsible for the high antioxidant activities of the ethyl acetate and methanol extracts of Garcinia daedalanthera Pierre leaves. Methods: In this study, the ethyl acetate extract was obtained by column chromatography, and the methanol extract was obtained by vacuum column chromatography. The mobile phase comprised n-hexane, ethyl acetate, and methanol with increased polarity. Antioxidant activity was examined using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The fraction with the highest antioxidant activity was purified through column chromatography, recrystallization, and preparative thin-layer chromatography. This fraction, termed the isolate of B, was identified using DPPH and AlCl3, and its antioxidant activity was quantitatively tested. Results: From this research, 21.7 mg of the isolate of B were obtained with an IC50 of 5.82 Î¼g/mL. Identification using an AlCl3 sprayer produced yellow phosphorescent spots under UV light. UV-Vis spectrum analysis revealed the presence of an aromatic compound and conjugated double bonds. Infrared spectrum analysis revealed the presence of âˆ’OH, Câ€“H alkane, C=C aromatic, C=O, and C-O-C groups. Conclusion: Based on this research, 21.7 mg of the isolate of B was derived through fractionation of the methanol extract, and this isolate exhibited antioxidant activity with an IC50 of 5.82 Î¼g/mL. The isolate of B was considered to be a flavonoid, as it was fluorescent under UV light (366 nm) after being sprayed with AlCl3 reagent.